2019
DOI: 10.22266/ijies2019.0228.12
|View full text |Cite
|
Sign up to set email alerts
|

OLOA: Based Task Scheduling in Heterogeneous Clouds

Abstract: Cloud computing provides increased performance, scalability and is both cost efficient as well as low accounts for maintenance, which makes it a preferred choice when the dynamic allocation of resources is considered. Of the various advantages that cloud computing provides, task scheduling is an essential feature that helps to boost performance and reduce operation cost. In the proposed OLOA, a solution is provided for optimization, taking the makespan and cost as major constraints. This is accomplished using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 18 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Previous task-planning techniques, such as GA and PSO techniques, are contrasted to the lion optimization. With WTA, researchers and scientists have access to a massive database of workflow traces that accurately reflect the functioning of actual scientific processes/workflows [24]. These traces are utilized to build DRL models that can learn to optimize resource allocation and job scheduling for comparable processes in cloud computing.…”
Section: International Journal On Recent and Innovation Trends In Com...mentioning
confidence: 99%
“…Previous task-planning techniques, such as GA and PSO techniques, are contrasted to the lion optimization. With WTA, researchers and scientists have access to a massive database of workflow traces that accurately reflect the functioning of actual scientific processes/workflows [24]. These traces are utilized to build DRL models that can learn to optimize resource allocation and job scheduling for comparable processes in cloud computing.…”
Section: International Journal On Recent and Innovation Trends In Com...mentioning
confidence: 99%
“…In [10] Services offered by the cloud computing are features that try to increase the scalability and performance at the same time, these features are efficient in terms of cost and minimum in terms of maintenance of account which makes the cloud a favoured option when allocation is done dynamic for the allocation of resources. Among the various benefits the cloud provides, the scheduling of task is an important attribute which helps to decrease the cost for operation at the same time increases the performance.…”
Section: Related Workmentioning
confidence: 99%
“…Various techniques have been developed to address this issue, for example, min-min, first come first serve (FCFS), max-min and minimum completion time techniques. Despite their adoption in many CC systems, some research has shown that these algorithms are unsuitable for scheduling large amounts of data [14]- [16].…”
Section: Introductionmentioning
confidence: 99%